The Roles of the Actin Cytoskeleton in Fear Memory Formation - Lamprecht, Raphael (Frontiers in Behavioral Neuroscience, 2011)
The formation and storage of fear memory is needed to adapt behavior and avoid danger during subsequent fearful events. However, fear memory may also play a significant role in stress and anxiety disorders. When fear becomes disproportionate to that necessary to cope with a given stimulus, or begins to occur in inappropriate situations, a fear or anxiety disorder exists. Thus, the study of cellular and molecular mechanisms underpinning fear memory may shed light on the formation of memory and on anxiety and stress related disorders. Evidence indicates that fear learning leads to changes in neuronal synaptic transmission and morphology in brain areas underlying fear memory formation including the amygdala and hippocampus. The actin cytoskeleton has been shown to participate in these key neuronal processes. Recent findings show that the actin cytoskeleton is needed for fear memory formation and extinction. Moreover, the actin cytoskeleton is involved in synaptic plasticity and in neuronal morphogenesis in brain areas that mediate fear memory. The actin cytoskeleton may therefore mediate between synaptic transmission during fear learning and long-term cellular alterations mandatory for fear memory formation.